Characteristics and Clinical Outcomes of Patients with Vasculitis Associated with Antibodies Against Neutrophil Cytoplasm in two Hospitals in Medellín, Colombia (2024)
ABSTRACT: Introduction: Vasculitis associated with antibodies against neutrophil cytoplasm (AAV) are rare diseases of autoimmune origin with local and/or systemic involvement, and a high rate of morbidity and mortality. There is little data on these diseases in Latin America and Colombia. Objectives: We describe the clinical characteristics, treatment, clinical outcomes and factors associated with all-cause mortality in patients diagnosed with AAV in Medellín, Colombia. Methods: An analytical observational study was designed to describe a retrospective cohort. Patients with diagnoses of granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), eosinophilic granulomatosis with polyangiitis (EGPA) and ANCA vasculitis limited to kidney (AAV-LR) who were hospitalized in two reference centers between 2014 and 2022 were included. The AAVs characteristics were compared, survival analyzes were performed and factors associated with all-cause mortality were searched. Results: Of 139 patients, the median age was 58 years (IQR 46-67). 51.5% were women. There were 71 patients (51.8%) with GPA, 42 (30.4%) with MPA, 14 (10.1%) with EGPA, and 11 (7.9%) with AAV-LR. Renal involvement was found in 101 (73.2%) with extra capillary glomerulonephritis in 63.9%. Antibodies against myeloperoxidase (anti-MPO) were the most common in 67.9% of patients. Mortality from any cause was 37.7%. The factors associated with higher mortality from any cause were an age at admission > 65 years (HR: 1.04 95% CI 1.01 - 1.06), pulmonary (HR: 2.32 95% CI 1.17 - 4.60) and gastrointestinal involvement (HR: 2.59 95% CI 1.09 - 6.14). Kaplan-Meier analyses showed lower survival in men, MPA, and those with renal and cardiovascular involvement. The most frequently used treatments were glucocorticoids and cyclophosphamide. Conclusions: In this AAV cohort, GPA was the most frequent phenotype, and the commonest antibody was anti-MPO. Higher mortality from any cause was documented compared to other cohorts.